Untreated Hypertension and Subsequent Incidence of Colorectal Cancer: Analysis of a Nationwide Epidemiological Database - Hidehiro Kaneko (Wiley, 2021)
Background Studies of the association of hypertension with incident colorectal cancer (CRC) may have been confounded by including individuals taking antihypertensive medication, at high risk for CRC (ie, colorectal polyps and inflammatory bowel disease), or with shared risk factors (eg, obesity and diabetes). We assessed whether adults with untreated hypertension are at higher risk for incident CRC compared with those with normal blood pressure (BP), and whether any association is evident among individuals without obesity or metabolic abnormalities. Methods and Results Analyses were conducted using a nationwide health claims database collected in the JMDC Claims Database between 2005 and 2018 (n=2 220 112; mean age, 44.1±11.0 years; 58.4% men). Participants who were taking antihypertensive medications or had a history of CRC, colorectal polyps, or inflammatory bowel disease were excluded. Each participant was categorized as having normal BP (systolic BP [SBP]<120 mm Hg and diastolic BP [DBP] <80 mm Hg, n=1 164 807), elevated BP (SBP 120–129 mm Hg and DBP <80 mm Hg, n=341 273), stage 1 hypertension (SBP 130–139 mm Hg or DBP 80–89 mm Hg, n=466 298), or stage 2 hypertension (SBP ≥140 mm Hg or DBP ≥90 mm Hg, n=247 734). Over a mean follow‐up of 1112±854 days, 6899 incident CRC diagnoses occurred. After multivariable adjustment, compared with normal BP, hazard ratios for incident CRC were 0.93 (95% CI, 0.85–1.01) for elevated BP, 1.07 (95% CI, 0.99–1.15) for stage 1 hypertension, and 1.17 (95% CI, 1.08–1.28) for stage 2 hypertension. The hazard ratios for incident CRC for each 10‐mm Hg‐higher SBP or DBP were 1.04 (95% CI, 1.02–1.06) and 1.06 (95% CI, 1.03–1.09), respectively. These associations were present among adults who did not have obesity, high waist circumference, diabetes, or dyslipidemia. Conclusions Higher SBP and DBP, and stage 2 hypertension are associated with a higher risk for incident CRC, even among those without shared risk factors for CRC. BP measurement could identify individuals at increased risk for subsequent CRC.